Penerapan Pola Hidup Bersih dan Sehat dengan Metode Groupwork untuk Warga di Parbaba Samosir - Rensina Griselda; Erni Asneli Asbi; Fajar Utama Ritonga (JOURNAL SAINS STUDENT RESEARCH, 2024)
. Implementing a clean and healthy lifestyle in the household is certainly needed to keep family members healthy. Government agencies such as the Health Service and also the Social and Empowerment Service continue to promote the PHBS program to Indonesian citizens. Good cooperation must be implemented in each household. By implementing a clean and healthy lifestyle, it can become a new habit for the residents of Parbaba Samosir. This activity was carried out as one of the mini projects of the Field Work Practice 2 activity which was carried out at the Samosir Social Empowerment Service. This activity was carried out for residents around Parbaba. This Field Work Practice activity was carried out for approximately 3 months. The method used in this research is the Groupwork method with general stages (1) Preparation, (2) Assessment, (3) Alternative Program Planning, (4) Action Plan Performance, (5) Program Implementation, (6) Evaluation and Results of Changes and (7) Termination.